2022
DOI: 10.3390/ma15196759
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Micro-Alloying and Surface Finishes on the Thermal Cycling Reliability of Doped SAC Solder Alloys

Abstract: The surface finish (SF) becomes a part of the solder joint during assembly and improves the component’s reliability. Furthermore, the SF influences the solder joint’s reliability by affecting the thickness of the intermetallic compound (IMC) layer at the solder interface and copper pads. In this experiment, five different alloys are used and compared with the SAC305 alloy, two of which, Innolot and SAC-Bi, are bi-based solder alloys. This study includes three common SFs: electroless nickel immersion gold (ENIG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…As a commonly used microalloying element in SnAgCu (SAC) and SnCu solder alloy, Ge functions as an anti-oxidant and improves the wetting performance of the alloy. The addition of Ge reduces the aging degradation and prohibits IMC overgrowth [33,34]. Hasnine et al [33] researched the effect of high-temperature storage on the microstructural and mechanical behavior of SnCu solder alloys with doped Ge.…”
Section: Introductionmentioning
confidence: 99%
“…As a commonly used microalloying element in SnAgCu (SAC) and SnCu solder alloy, Ge functions as an anti-oxidant and improves the wetting performance of the alloy. The addition of Ge reduces the aging degradation and prohibits IMC overgrowth [33,34]. Hasnine et al [33] researched the effect of high-temperature storage on the microstructural and mechanical behavior of SnCu solder alloys with doped Ge.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the environmental and health risks of lead, it is being phased out and replaced by a new semi-eutectic solder alloy. Microalloying with nickel (Ni), bismuth (Bi), antimony (Sb), indium (In), and other elements could enhance the performance of solder alloys [ 1 ]. Although extensive studies have been performed on the mechanical and thermal characteristics, including fatigue of various solder alloys using accelerated test conditions, the reliability of solder joints in real service requires further investigation to be better understood.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of stress or aging conditions, SAC-Bi was shown to have a longer fatigue life than SAC305. Other analyses have scrutinized the shear fatigue characteristics of SAC-based micro-alloys with Bi, Ni, and Sb under various organic solderability preservatives (OSP) and immersion silver (ImAg) surface finishes [ 1 ]. It was observed that the greater the Ag content, the better the fatigue and shear strengths achieved [ 4 ].…”
Section: Introductionmentioning
confidence: 99%